UJI SITOKSISITAS CAMPURAN RESIN AKRILIK DENGAN KITOSAN SEBAGAI BAHAN GIGI TIRUAN ANTI JAMUR - Titik Ismiyati; Widowati Siswomihardjo; Marsetyawan H.N.E. Soesatyo; Rochmadi Rochmadi (Jurnal Teknosains, 2016)
Denture acrylic resin contain monomer residue that can cause allergic reactions and inflammation in the mouth. Chitosan has advantage biocompatible and antifungal. The purpose of this study was to examine toxicity acrylic resin blends with chitosan as denture antifungal in fibroblast cell culture. This study uses chitosan concentration 0.5%, 1%, 2% and 4% of 2.5 ml were blends with acrylic resin. Fibroblast cell cellular responses were assessed using MTT assay. Data at the cell viability analyzes used Anova one path (p <0.05). The results showed the greatest average adsorbansi fibroblast cell in blends acrylic resin was chitosan concentration of 0.5% (0.434 ± 0.119) with 99.810% cell viability, and the smallest average chitosan concentration of 4% (0.385 ± 0.023) and 88.523% cell viability. Anova test showed there were differences the effect of varying concentrations of chitosan significantly to adsorbansi and cell viability (p <0.05). The results of post hoc test showed a concentration of 4% was significantly different than other concentration. Conclusion, acrylic resin blends with chitosan at a concentration of 0.5%, 1%, 2% were non-toxic, being mild toxic concentration of 4%.